Paroxysmal and cognitive phenotypes in Prrt2 mutant mice. (1st April 2019) - Robertson, Louise; Featherby, Travis; Howell, Stuart; Hughes, James; Thomas, Paul
Abstract : Mutations in proline‐rich transmembrane protein 2 ( PRRT2 ) cause a range of episodic disorders that include paroxysmal kinesigenic dyskinesia and benign familial infantile epilepsy. Mutations are generally loss of function and include the c649dupC frameshifting mutation that is present in around 80% of affected individuals. To investigate how Prrt2 loss of function mutations causes disease, we performed a phenotypic investigation of a transgenic Prrt2 knockout ( Prrt2 KO) mouse. We observed spontaneous paroxysmal episodes with behavioural features of both seizure and movement disorders, as well as unexplained deaths in KO and HET animals. KO mice showed spatial learning deficits in the Morris water maze, as well as gait abnormalities in the quantitative Digigait analysis; both of which may be representative of the more severe phenotypes experienced by homozygous patients. These findings extend the described phenotypes of Prrt2 mutant mice, further confirming their utility for in vivo investigation of the role of Prrt2 mutations in episodic diseases. Abstract : Homozygous Prrt2 knockout mice display paroxysmal phenotypes and survival defects.